Small Business Capital Structure Choice - Jacques A. Schnabel (Journal of Small Business Finance, 1992)
A simple single-period model of entrepreneurial capital structure choice under conditions of informational asymmetry is developed. The uncertain terminal cash flow generated by a business venture is assumed to depend on both the amount of effort provided by the entrepreneur and the quality of the business venture. External financing induces the effort-averse entrepreneur to reduce the amount of effort he exerts. However, by astute choice of capital structure, the entrepreneur can mitigate this effect. It is shown that this entails financing high quality ventures with debt and low quality ventures with equity. This explains the predominance of debt in the capital structures of small firms.
Keywords: L25; G32; M13; 650; Capital Structure; Capital; Small Business; Small Firm